Chapter Il ricettario gesuato lucchese del 1562: prime osservazioni linguistiche - BIFFI, MARCO (Fragmentaria. Studi di storia culturale e antropologia religiosa, 2020)
The contribution examines the Libro de i secretti et ricette, composed in 1562 by Frate Giovanni Andrea de Farre, which constitutes an interesting testimony of specialistic language related to pharmacology between the Middle Ages and the Modern Age. It focuses mainly on a quantitative analysis of the lexicon and on the potentialities for research through the creation of a glossary. It also dwells on some linguistic features functional to the identification of possible diachronic and diatopic stratificated layers of the text, probably related to written and oral recipes of various origins.